Use of Recycled Concrete Aggregate in Controlled Low-Strength Material (CLSM) - Naganathan S.; Mustapha K.N.; Omar H. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Use of recycled concrete aggregate (RCA) is getting importance as it minimizes the use of fresh materials and eliminates waste disposal. One of the uses of RCA is as aggregate in Controlled Low Strength Material (CLSM). This paper reports the results of the investigation done on the use of RCA in CLSM. Various mixtures of CLSM were made using RCA, fly ash, and cement. Tests for workability, bleeding, density, strength, water absorption, sorption, and ultrasonic pulse velocity (UPV) were conducted. Results show that the compressive strength ranged from 1.71 MPa to 4.92 MPa, fresh density from 1879 kg/m3 to 1998 kg/m3. The strength of CLSM increases with the increase in fly ash; water absorption and bleeding decrease with increase in fly ash. It is concluded that the RCA has potential to be used in CLSM and the addition of fly ash enhances the performance.